2022
DOI: 10.1186/s12915-022-01234-1
|View full text |Cite
|
Sign up to set email alerts
|

Mating behavior and reproductive morphology predict macroevolution of sex allocation in hermaphroditic flatworms

Abstract: Background Sex allocation is the distribution of resources to male or female reproduction. In hermaphrodites, this concerns an individual’s resource allocation to, for example, the production of male or female gametes. Macroevolutionary studies across hermaphroditic plants have revealed that the self-pollination rate and the pollination mode are strong predictors of sex allocation. Consequently, we expect similar factors such as the selfing rate and aspects of the reproductive biology, like the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…This result suggests that we can probably interpret variation in SA among field-collected worms of different Macrostomum species as being at least partially due to interspecific variation, even if they happen to have been sampled from different group sizes, and may therefore also vary in part due to SA plasticity. Thus, although we cannot currently explain the observed interspecific variation in SA among the species studied here, our study will facilitate research in understanding the evolution of SA patterns across Macrostomum species, by allowing future studies to include SA estimates from field-collected worms (such as in Brand et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that we can probably interpret variation in SA among field-collected worms of different Macrostomum species as being at least partially due to interspecific variation, even if they happen to have been sampled from different group sizes, and may therefore also vary in part due to SA plasticity. Thus, although we cannot currently explain the observed interspecific variation in SA among the species studied here, our study will facilitate research in understanding the evolution of SA patterns across Macrostomum species, by allowing future studies to include SA estimates from field-collected worms (such as in Brand et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Although this prediction is consistent with our results, changes in sex-specific fitness are unlikely to be mediated by changes in ovary size, since relative ovary area showed a tendency to be negatively related to fitness via the female sex role (figure 3B). Nevertheless, a handful of studies have successfully demonstrated trade-offs between male and female sex function in this and other species (Schärer 2009, Di Bona et al 2015, Picchi and Lorenzi 2019, Brand et al 2022, so perhaps ovary area does not capture the most important aspects of investment in the female sex role. This is in line with results from Janicke et al…”
Section: Rapid Evolution Of Female-specific Fitnessmentioning
confidence: 93%
“…Finally, mating frequency (and possibly mating duration) could be positively correlated with allocation towards the male function (e.g., testes). Indeed, studies in Macrostomum have shown interspecific variation in sex allocation towards the male and female functions, such as testes and ovaries (Singh et al, 2020b;Brand et al, 2022a;Singh & Schärer, 2021). This interspecific variation could potentially relate to the mating behaviour, as we can expect species that have a longer mating duration or higher mating frequency to have larger testes, if longer and/or more frequent mating implies that more sperm are transferred (Janicke & Schärer, 2009).…”
Section: Evolution Of the Mating And Suck Behaviour Across The Genus ...mentioning
confidence: 99%
“…Species in the genus Macrostomum are small (~0.3 to 3.0 mm body length) aquatic free-living flatworms that are highly transparent, permitting detailed observations of internal structures (for the general morphology see Figure 1A,B). The sperm and eggs are produced in the paired testes and paired ovaries, respectively, with studies documenting inter-and intra-specific variation in both testis and ovary size across the genus (Singh et al, 2020b;Brand et al, 2022a;Singh & Schärer, 2021). The female antrum is located anterior to the male antrum, connected to the outside, respectively, via a female genital opening (also female genital pore or vagina) and the male genital opening (also male genital pore).…”
Section: Study Organismsmentioning
confidence: 99%
See 1 more Smart Citation